Association Between Adiposity and Left Ventricular Mass in Children With Hypertension. Issue 7 (4th November 2015) - Brady, Tammy M.; Appel, Lawrence J.; Holmes, Kathryn W.; Fivush, Barbara; Miller, Edgar R.
Abstract : Left ventricular hypertrophy (LVH) is prevalent among hypertensive children; however, blood pressure (BP) does not predict its presence. The authors conducted a 1‐year prospective cohort study to examine the hypothesis that obesity‐related risk factors are associated with left ventricular mass index (LVMI) in hypertensive children, and the association between adiposity and LVMI is mediated by BP‐dependent and ‐independent pathways. A total of 49 hypertensive children were enrolled: 51% were overweight/obese and 41% had LVH at baseline. Children overweight/obese at baseline and follow‐up had a greater LVMI increase than those of healthy weight at each visit: mean change of 6.4 g/m 2.7 vs 0.95 g/m 2.7 . Baseline body mass index z score was independently associated with LVMI change (β=4.08, 1.54–6.61; P =.002). Only pulse pressure and serum aldosterone partially mediated this relationship. Hypertensive youth manifest multiple cardiovascular disease risk factors that worsen over time despite treatment. Of these, adiposity is most associated with LVH and increasing LVMI.